Investigating the linkage between knowledge sharing attitude, self-efficacy, and behavior in Bangladeshi information technology sector: Knowledge sharing intention as a mediator - Lima Nasrin Eni; Susmita Saha; Md Alamgir Hossain; Mohammad Mizenur Rahaman (Heliyon)
The research aims to investigate how employees' knowledge-sharing behavior (KSB) is affected by knowledge-sharing attitude (KSA) and knowledge-sharing self-efficacy (KSSE) when knowledge-sharing intention (KSI) is a mediator at IT companies in Bangladesh, using the widely accepted Theory of Planned Behavior as the underlying research framework. This investigation is explanatory in nature which emphasizes on the link among variables and follows quantitative research method. Data was assembled in google form applying convenience sampling from 295 employees working in seven IT companies of Bangladesh. The data was statistically analyzed by using partial least square-structural equation model (PLS-SEM) method. The results revealed that knowledge sharing attitude and knowledge sharing self-efficacy of employees’ significantly affect their knowledge sharing intention and knowledge sharing behavior. Furthermore, there is a mediating impact on the relationship between knowledge sharing attitude and knowledge sharing behavior, and knowledge sharing self-efficacy and knowledge sharing behavior when knowledge sharing intention plays as a mediator. This paper contributes to existing literature regarding knowledge sharing intention and knowledge sharing behavior and offers policymakers an understanding on knowledge sharing attitude and knowledge sharing self-efficacy that driving knowledge sharing behavior among Bangladeshi IT personnel to achieve desired organizational goals.